Protective effects of pulp and kernel oils from Canarium odontophyllum fruit in normal and hypercholesterolemic rabbits - Shakirin, Faridah Hanim; Azlan, Azrina; Khoo, Hock Eng; Ismail, Amin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
This study aimed to determine the protective effects of CO pulp and kernel oils supplementation to normocholesterolemic and hypercholesterolemic rabbits. Rabbits from the treatment groups were supplemented with CO pulp and kernel oils for four weeks. Bloods were drawn from all experimental groups at baseline and fourth week to determine protective effects of CO oils supplementation on plasma total antioxidant status (TAS) and catalase (CAT) activity. Liver function tests (ALT, AST, and GGT activities) were also determined for all the groups. The results showed that CO oil supplementation increased plasma TAS in both normal and hypercholesterolemic groups. Plasma CAT activities in the hypercholesterolemic groups supplemented with CO oils were significantly reduced but not for the normocholesterolemic groups. Significant reduction of plasma AST was observed for the hypercholesterolemic rabbits given CO pulp and kernel oils compared with the hypercholesterolemic control rabbits, but not for plasma ALT and GGT. In the normocholesterolemic rabbits, CO pulp oil had caused a significant elevation of plasma ALT, AST, and GGT levels as compared to the negative control rabbits. Therefore, CO pulp and kernel oils are somehow not hepatotoxic, and the oils are potent functional foods.